Atividade antimalárica de bioprodutos de plantas medicinais brasileiras ou moléculas sintetizadas avaliadas contra Plasmodium Falciparum in Vitro e contra Plasmodium Berghei in Vivo - Isabela Oliveira de Freitas (2011)
The selection and spread of multidrug-resistant P. falciparum to available antimalarial drugs and recently chloroquine-resistant P. vivax makes necessary the search and develop of new drugs. The main drugs used to treat human malaria, quinine and artemisinin, are isolated from medicinal plants, reinforcing the importance of ethnopharmacology, used in this study. The antimalarial activities of Brazilian medicinal plants were evaluated using extracts of "falsas quinas", Symphyopappus sp, Aspidosperma sp, and Kielmeyera variabilis and of synthetic molecules. They were tested in vitro against blood forms of P. falciparum, clone W2, chloroquine-resistant; some compounds were also tested in vivo against P. berghei. The in vitro methods to assess antimalarial activity were the traditional test, using optical microscopy, and hypoxanthine assay with radioisotope uptake by the parasite. The first is subject to human error of interpretation and slow reading, while the hypoxanthine test is semi-automatic and presents fast reading, a rapid method that generates more accurate dose-response curves. In parallel, cytotoxicity tests were performed with HepG2 cells, and the index of selectivity calculated. Among 26 samples of falsas quinas, only one (Q26) was active in vitro and in vivo, the Remijia ferruginea; the extracts and fractions from Symphyopappus sp were also active. Samples of three species of Aspidosperma sp were active, i.e., the extracts of the branch/stem, stem bark of APM, and stem of APT (IC50 ~ 6g/mL) in hypoxanthine test; the crude bark root extract of APP and its fractions (acetylated, aqueous, AP5 and AP5 ALC) with IC50 values between 3.4 and 8.8g/mL in hypoxanthine assays. Some samples of K. variabilis were also very active allowing the isolation of pure compounds and subfractions. The traditional test (72h incubation) showed a higher sensitivity than the hypoxantine test for detection of antimalarial activity. However, if conducted in the same incubation time, both hypoxanthine and traditional assays (42h) resulted in similar rates of activities. We conclude that hypoxanthine test is the ideal in the search for antimalarial drugs on a large scale, requiring determination of cytotoxicity of the active samples for selection of those with better selectivity index. Some herbal extracts were shown to be toxic.